DEVELOPMENT OF COMIC-BASED LEARNING MEDIA ON INDONESIAN HISTORY MATERIALS DURING THE NATIONAL MOVEMENT PERIOD TO IMPROVE LEARNING MOTIVATION OF GRADE XI STUDENTS OF RIAU OIL AND GAS TECHNOLOGY VOCATIONAL SCHOOL: Pengembangan Media Pembelajaran Berbasis Komik Materi Sejarah Indonesia Masa Pergerakan Nasional Untuk Meningkatkan Motivasi Belajar Siswa Kelas XI SMK Migas Teknologi Riau - Afifah Miftahul Jannah; Bunari; Yanuar Al Fiqri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to develop comic-based learning media for the Indonesian History material during the National Movement Period to increase the learning motivation of grade XI students of SMK Migas Teknologi Riau. The background of this study is based on the low learning motivation of students caused by the use of monotonous learning media, such as printed books with minimal visuals. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The results of media validation by material experts obtained a score of 90% and by media experts 90%, both in the very good category. A small group trial with 7 students showed a strongly agree score of 81%, categorized as adequate, while a large group trial with 20 students obtained a score of 88%, categorized as very adequate. Furthermore, there was an increase in the percentage of learning motivation scores between the small group from 80% to 84%, while the large group from 71% to 82% after using comic media. These results indicate that comic media is effective in increasing student learning motivation in history learning. The novelty of this research lies in the contextual integration of comic visual media into national history material, a practice never before implemented in this school. This medium not only captures students' attention but also makes learning more meaningful and enjoyable.